Avaliação de incontinência anal e urinária em mulheres atletas - Gomes, Natalia Tavares [UNIFESP] (2019)
Objective:The aims wasto determinethe role of high-level sport practice on anal incontinence (AI) and urinary incontinence (UI) in a young nullliparous female.Settings/Patients: case- control study that included 136 women (85 athletes and 51 sedentary) invited to respond questions extracted from validated questionnaires specific to anal incontinence and urinary incontinence. Results: The groups were homogeneous as to age and educational level. The prevalence of anal incontinence was statistically higher in the athletesgroup than in the sedentary group (68,2% versus 13,7%, p<0,001). Between the athletes with AI, 96,5% were classified as anal incontinence (OR=13,03, p<0,001), involuntary loss of gas was more frequent symptom reported. The UI risk was higher in female athletes than control group (34,1% versus 5,9%, p<0,001). Conclusion: The study evidenced a strong correlation between the high- level sport and risk for AI and UI.